Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content: 1. The relationship of the science of jurisprudence with theology - jurisprudence and jurisprudence rules Dr. Jarallah Abdullah Ahmed Aljarallah 2. Irrevocable divorce, BaynunahSoghra, before Sharia courts inside the Green Line (An analytical study) Dr. Mohammed Saeed Zahra, Dr. Abdullah Jamil Abu Wahdan 3. Climate Change and Legal Responsibility: Challenges and Solutions from the Perspective of Environmental Jurisprudence Mrs. Muna Ateeq Rubayea Aldarmaki 4. Conditions of Comprehensiveness and Distinction in Juristic Definitions Mrs. Amal Tariq Al-Omar